Revitalizing Communities: Proposing Mosque-Driven Circular Economy Empowerment Model - Mutmainah, Lu'liyatul; Andani, Listia; Susilawati, Ela (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The mosque has so far been known only as a place of worship such as prayer and recitation by Muslims. History records that during the time of the Prophet, the mosque was also the center of government, economic center, education center, and others. Some mosques are also tourist areas that provide more economic value so that they can improve people's welfare. However, tourist areas often cause problems related to waste, water use, and others. Understanding of the circular economy that can provide sustainable benefits is still not widely known and implemented, including for managing mosques. This study aims to analyze and propose an optimization model for mosque-based circular economic empowerment to achieve a sustainable economy. The research uses a qualitative approach with literature studies and in-depth interviews with related parties. The results of the study show that empowering mosques based on a circular economy will not only have a positive impact on places of worship but also the economic, social, and environmental sectors. For example, managed mosque waste can provide economic value. In addition, the use of ablution water can be reused for land irrigation and fish farming. The synergy between the government, universities, communities, and the industrial world can be carried out to implement this mosque-based circular economy. The results of this study can be used as a basis for recommendations and a pilot project for implementing mosque-based circular economic empowerment.